Outcomes of microvascular free tissue transfer in twice‐irradiated patients. Issue 6 (9th January 2017) - Clancy, Kate; Melki, Sami; Awan, Musaddiq; Li, Shawn; Lavertu, Pierre; Fowler, Nicole; Yao, Min; Rezaee, Rod; Zender, Chad A.
Abstract : Background: Patients may require microvascular free tissue transfer (MFTT) following re‐irradiation for recurrent cancer or radiation complications. The objective of this study was to describe the indications for and outcomes of free flaps performed in twice‐radiated patients. Methods: A retrospective chart review identified the indications for and outcomes of 36 free flaps performed on 29 twice‐irradiated patients. Results: The free flap success rate was 92%. The most common indications requiring MFTT were cancer recurrence and osteoradionecrosis. Sixty‐one percent experienced postoperative complications, most commonly wound infection (33%). Twenty‐five percent of the procedures required return to the operating room due to postoperative complication. Conclusions: MFTT can be successfully performed in the twice‐irradiated patient population with a success rate comparable to singly‐radiated patients. Despite a high success rate, there is also a high rate of surgical site complications, especially infection.